Molecular Detection of Mucor Circinelloides in Diabetic Patients - Abbas M. Ammari, Anaam Fuad Hussein, Fakhar Al-Nissaa Zaid Kaerm, (Pakistan Journal of Medical & Health Sciences, 2022)
Workload Aims: This study was aimed to detect of Mucor circinelloides in diabetic patients and compare between the cultural and molecular methods for rapid and efficiency detection Materials and Methods: A total of one hundred specimens were collected from patients with diabetes mellitus who attended medical city in Baghdad for a period of four months. Clinical diagnosis were done by physician. The specimens were classified as (Blood, Cutaneous and sputum). According to the gender, the specimens were sixty eight males and thirty two females. Different cultural and molecular detection methods were used for identification of M. circinelloides. Results: Five isolates of M. circinelloides were identified using different cultural media and PCR method. The molecular weight of M. circinelloides bands using PCR method was ~650 bp. Depending on PCR sequencing method, only one isolate was showed substitution mutation in amino acid is (I). Conclusions: The efficacy of used different cultural methods and molecular methods to isolate M. circinelloides were similar but, molecular methods are less time consuming.